Christian Love to God According to “Sermon on the Divine and Holy Love” by Theodore of Cyrus - Milanov, Rossen (Forum Theologicum Sardicense, 2025)
Rossen Milanov, Christian Love to God According to "Sermon on the Divine and Holy Love" by Theodoret of Cyrus. The love for God is the greatest Christian virtue and has been subject of numerous writings in Christian antiquity. In his Sermon on the Divine and holy love, blessed Theodoret of Cyrus († c. 457 AD) explores the motivation behind the supernatural deeds of biblical heroes and Christian monks, attributing them to their love for God. It wounds sweetly, provokes a yearning for God, and feeds and warms the loving person. It introduces one into a new, eternal world. Every Christian is called to experience this love in the present world, and the perfection of this love is a process that continues throughout eternity.